Study on decision support system of agricultural mechanization based on GIS - ZHENG Wen-zhong; HE Yong; ZHANG Yu-lin (浙江大学学报. 农业与生命科学版)
According to analysis of integration methods between geographical information system (GIS) and application model, a decision support system (DSS) based on GIS for agricultural mechanization management was designed by means of systematic analysis, information processing technology, system integration methods, database technology etc. Then, integration of GIS and DSS was implemented with the help of database development software Visual Basic 6.0 and professional MapInfo 7.0 GIS. The system was developed with the functions of information inputs, modification, inquiry, erasing, statistic analysis, prediction, accessory decision, congruence of thematic map and outputs, and providing new means of scientific forecast and decision for agricultural machinery management department.